Phytochemical Findings Evidencing Botanical Origin of New Propolis Type from North‐West Argentina. Issue 5 (4th April 2019) - González, Mariela; García, María E.; Slanis, Alberto; Bonini, Ana; Fiedler, Stephanie; Fariña, Laura; Dellacassa, Eduardo; Condurso, Concetta; Lorenzo, Daniel; Russo, Marcos; Tereschuk, María L.
Abstract: Propolis samples from north‐west Argentina (Amaicha del Valle, Tucumán) were evaluated by palynology, FT‐IR spectra, and RP‐HPTLC. In addition, the volatile fraction was studied by HS‐SPME‐GC/MS. The botanical species most visited by Apis mellifera L. near the apiaries were collected and their RP‐HPTLC extracts profiles were compared with propolis samples. In addition, GC/MS was performed for volatile compounds from Zuccagnia punctata Cav. (Fabaceae). FT‐IR spectra and RP‐HPTLC fingerprints of propolis samples showed similar profiles. In RP‐HPTLC analyses, only Z. punctata presented a similar fingerprint to Amaicha propolis. The major volatile compounds present in both were trans‐ linalool oxide (furanoid), 6‐camphenone, linalool, trans ‐pinocarveol, p ‐cymen‐8‐ol, and 2, 3, 6‐trimethylbenzaldehyde. Potential variations for the Amaicha del Valle propolis volatile fraction as consequence of propolis sample preparation were demonstrated. Abstract :